2016
DOI: 10.1111/dar.12387
|View full text |Cite
|
Sign up to set email alerts
|

Addressing gaps on risk and resilience factors for alcohol use outcomes in sexual and gender minority populations

Abstract: Issues In 2011, the Institute of Medicine (IOM) released a report that constituted the first comprehensive effort by a federal body to understand the current state of science pertinent to the health needs of sexual and gender minority populations. This mini-review summarises recent empirical, methodological and theoretical advances in alcohol-related research among to lesbian, gay, bisexual and transgender populations and highlights progress toward addressing gaps, with a particular interest in those identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 116 publications
4
60
3
Order By: Relevance
“…Nearly all were found among bisexual-identified youth and students with both male and female sexual partners; these sexual minority individuals had up to twice the odds of engaging in alcohol use behaviors when compared with sexual majority students. This is consistent with numerous prior studies that have found that bisexual individuals are disproportionately likely to use drugs and alcohol, even in comparison with gay and lesbian individuals (Drabble et al, 2013; Green and Feinstein, 2012; Hughes et al, 2010; Hughes et al, 2014; Talley et al, 2016). …”
Section: 0 Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nearly all were found among bisexual-identified youth and students with both male and female sexual partners; these sexual minority individuals had up to twice the odds of engaging in alcohol use behaviors when compared with sexual majority students. This is consistent with numerous prior studies that have found that bisexual individuals are disproportionately likely to use drugs and alcohol, even in comparison with gay and lesbian individuals (Drabble et al, 2013; Green and Feinstein, 2012; Hughes et al, 2010; Hughes et al, 2014; Talley et al, 2016). …”
Section: 0 Discussionsupporting
confidence: 92%
“…Similar results have been found between sexual minority men and women (Chow et al, 2013), but they have not been fully consistent (Bariola et al, 2016). Among sexual minority adolescents, 2005 and 2007 YRBS data found that females were heavier alcohol users than males (Talley et al, 2016). As the contradictory data from some of these studies are nearly a decade old, perhaps this reflects changing dynamics in alcohol initiation and usage among youths.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Also similar to previous studies and meta-analyses [11,12,35], sexual minority girls demonstrated a greater number of disparities in alcohol use behavior across the 15-year time span than were observed in the comparisons between heterosexual and sexual minority boys. Furthermore, as with previous research, bisexual and mostly heterosexual youth in our study displayed greater risk for alcohol use behaviors across years when compared to their heterosexual peers, especially among females, while gay/lesbian youth did not differ from heterosexual youth in 23 of the 32 comparisons.…”
Section: Discussionsupporting
confidence: 85%
“…Sexual minority (i.e. lesbian/gay and bisexual [LGB]) youth represent an at-risk group for alcohol use and misuse during adolescence [11][12][13]. More than a decade of research demonstrates disproportionately high rates of alcohol use among LGB compared to heterosexual youth across multiple indicators of risk including: life-time alcohol use [14], early initiation [14,15], frequency of use [16,17], the participation in and frequency of heavy episodic drinking (HED) [14,18] and problems related to drinking [19].…”
Section: Introductionmentioning
confidence: 99%
“…The minority stress model, where stress mediates relationships between a stigmatized sexual identity and, in this case, alcohol use and consequences (Meyer, 2003; Talley et al, 2016), has some limitations in that it does not incorporate potential psychological mediators between stress and health outcomes (Hatzenbeuhler, 2009). It also fails to incorporate moderators such as gender.…”
Section: Discussionmentioning
confidence: 99%